A Sustainable Long-Term Health Care System for Aging China: A Case Study of Regional Practice. Issue 3 (3rd July 2017) - Lu, Bei; Mi, Hong; Zhu, Yanan; Piggott, John
Abstract: This article documents the Qingdao Long-term Care Medical Insurance (LTCMI) program and analyzes its recipient demographics, costs of program expansion and potential drivers of costs. About 10% of the program's clients received institutional care, while the rest received care at home or in other residential locations. More than 60% of recipients were aged 80 years and older. Analysis of exit (mostly due to mortality) patterns of clients from the Qingdao long-term care system suggests that exit rates were correlated with being older than 80 years at the time of joining, gender, types of long-term care being received (institutional or residential) and entry-level activities of daily living scores. The beneficiary recipient structure of the Qingdao LTC system suggests that under current per unit costs, expanding coverage to all would only cost about 0.1% of Gross Domestic Product in China. Such a system will not only provide frail elderly people with long-term medical care services, but also greatly relieve the pressure on hospitals caused by aging patients, and systematically distribute medical resources in the long run, thus contributing to its sustainability.